Rare Lipomatous Neoplasm of The Thigh in A 13 Year Old Male with A Discussion of Imaging Features and Differential Diagnosis of A Fatty Extremity Mass - Jamie T. Caracciolo; Evita Henderson-Jackson; John A. Churchill; Odion T. Binitie (Journal of Neoplasms, 2018)
Lipomatous tumors are among the most common primary musculoskeletal neoplasms affecting both pediatric and adult patient populations. Patient age, tumor location, and imaging features all contribute to the differential diagnosis of musculoskeletal tumors. Tumors identified outside of common patient demographics or in unusual locations may lead to preoperative misdiagnosis. We present an uncommon adipocytic tumor occurring at an uncommon age which was proven at surgery to represent a preoperatively unexpected diagnosis. A 13 year old male presented with a fatty anterior proximal thigh mass; age and magnetic resonance findings suggested lipoblastoma. However, following complete surgical resection, histopathology confirmed hibernoma, a benign lipomatous tumor characterized by the presence of white and multivacuolated brown fat cells, the vast majority of which occur in adult patients.
Keywords: pediatric